Impact of the endothelial nitric oxide synthase (eNOS) c.894 G > T gene polymorphism on coronary artery dilatation disease - Hany Tawfik Fathelbab; Adel Sayed Taie; Inas Abd-Elatif; Soheir Mahmoud Ibrahim; Ahmed Hossam Mowafy; Farouk Mostaf Faris (Egyptian Journal of Critical Care Medicine)
Abstract Purpose Coronary artery dilatation diseases, including coronary artery aneurysm (CAA) and coronary artery ectasia (CAE), are characterized by abnormal dilations of the coronary arteries. The endothelial nitric oxide synthase (eNOS) c.894G > T polymorphism has been implicated in reduced eNOS enzyme activity, potentially increasing susceptibility to coronary heart disease by altering nitric oxide (NO) bioavailability. While this polymorphism is one of the most extensively studied variations in the eNOS gene—leading to an amino acid substitution at position 298 from glutamic acid (GAG) to aspartic acid (GAT)—its role in coronary artery dilatation remains uncertain. This study investigates the association between the eNOS c.894G > T polymorphism and angiographically confirmed coronary artery dilatation (CAA/CAE), as well as its potential link to atherosclerotic coronary artery disease (ACAD). Methods A comparative study was conducted on 100 patients diagnosed with coronary disease who underwent coronary angiography between December 2018 and December 2021. Based on angiographic assessment and expert evaluation, patients were categorized into four groups: (1) normal coronary arteries (n = 25), (2) atherosclerotic CAD without coronary dilatation (n = 25), (3) CAA/CAE without atherosclerosis (n = 25), and (4) CAA/CAE with concomitant atherosclerotic CAD (n = 25). Genotypic analysis of the eNOS c.894G > T (Glu298Asp; rs1799983) polymorphism was performed using Real-Time polymerase chain reaction (PCR). Results The GG genotype was significantly more prevalent in the normal and atherosclerotic CAD groups (73.5% [n = 36] vs. 64% [n = 32], respectively), whereas the frequency of polymorphic genotypes (GT and TT) did not differ significantly between these groups (26.5% [n = 13] vs. 36% [n = 18], P = 0.31). In contrast, the presence of polymorphic genotypes (GT and TT) was markedly higher in patients with coronary artery dilatation (46.9% [n = 23]) compared to those without dilatation (16% [n = 8]), irrespective of atherosclerotic CAD status (P = 0.001). Conclusion The eNOS c.894G > T polymorphism is associated with an increased risk of coronary artery dilatation (CAA/CAE) but does not appear to contribute significantly to atherosclerotic coronary artery disease.